Close to the edge : how Yes's masterpiece defined prog rock - Romano, Will, 1970- (Mlwaukee, WI Backbeat Books, 2017)
The author draws upon dozens of original and past interviews to argue that Close to the edge is the ultimage prog rock album.
Cord of life: progressive rock begins -- Sweet dreams: early Yes -- The spiral aim: inside CTTE -- What's a Khatru? wordplay -- Valleys of endless seas: Roger Dean's floating world -- Seasons will pass you by: the (un)solid time of change -- The journey takes you all the way: breakthrough record, whirlwind touring -- They regard the summit: the impact of YES and CTTE.
Includes bibliographical references (pages 271-281), discography (pages 261-269) and index.
Keywords: Yes (Musical group); Yes (Musical group).; Progressive rock (Music) -- England -- History and criticism